2020
DOI: 10.46414/yasad.803533
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite öğrencilerinin yaşlı ayrımcılığına ilişkin tutumları ve yaşlı ayrımcılığını etkileyen faktörler

Abstract: This study aims to determine the attitudes of university students towards ageism and influencing these factors. The study was carried out with 1st and 2nd-grade students who have registered for the elderly care course given in the 2018-2019 education period fall term in a State University. Data collection tools comprised two sections: Sociodemographic Questionnaire Form and Ageism Attitude Scale (AAS). Descriptive statistics, linear regression, independent sample t-test, and oneway ANOVA were utilized to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…16 Güngör and Borazan carried out a study with elderly care and paramedic students and reported that the participants' negative attitudes towards elderly individuals were low and positive attitudes were high. 17 In the study conducted by Singh et al with health sciences students, it was stated that students have moderate knowledge and positive attitudes towards aging. 19 It was reported in another study that health and administrative staff working in the geriatric center have a positive attitude towards the elderly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Güngör and Borazan carried out a study with elderly care and paramedic students and reported that the participants' negative attitudes towards elderly individuals were low and positive attitudes were high. 17 In the study conducted by Singh et al with health sciences students, it was stated that students have moderate knowledge and positive attitudes towards aging. 19 It was reported in another study that health and administrative staff working in the geriatric center have a positive attitude towards the elderly.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there are just a few studies on the attitudes of elderly care students towards elderly individuals. [16][17][18] For this reason, it was also discussed with different groups on the subject.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation